“My daughter is a white girl in a mixed body that wishes she were black”: monoracial parents perceptions of mixed-race children and racial identity development - Mitchell, Yolanda T. (Kansas State University, 2014)
Racial identity of mixed race individuals is important to understand because of the growing proportion of the population with parents from different racial groups. Having more than one racial heritage has a direct impact on how these children are seen by others as well as how they understand and encounter the world around them. Parents socialize their children in matters of race and discrimination that can impact their racial identity development, which is a component of their overall identity development. The aim of this study was explore how multiracial children are socialized and the impact of that socialization on racial identity formation from a heuristic perspective. Heuristic inquiry is a facet of phenomenology that seeks to understand the researcher’s experience of the phenomenon; therefore, I provided data on my experiences with raising a mixed-race child in a monoracial family. Two other families experiencing the same phenomenon were also interviewed. Themes related to racial profiling, parental perception of the mixed race child’s personality, skin tone, level of respect, and parenting were identified through the five-step analysis process recommended by Moustakas for heuristic inquiry, including immersion, incubation, illumination, explication, and creative synthesis. This study highlights relevant aspects in the lives of mixed-race children, how that impacts the way society views mixed-race individuals, and how those individuals encounter the world around them.
Keywords: Multiracial families; Biracial identity; Racial identity development; Family ethnic socialization; Multiracial children; Racial socialization; Individual & Family Studies (0628)